EFEKTIVITAS PENERTIBAN RUMAH LIAR DI KOTA PEKANBARU - Marfuzoh "; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The city has a promising appeal, along with the development of an increasingly modern era with the progress of the city, unnoticed population growth continues to increase. Of course the level of problems that arise will also be higher, one of which is that there are still many illegal houses arround vacant land and public areas that are used as residences and places to sell. Therefore, the City of Pekanbaru needs to issue a policy in the form of Regional Regulation of the City of Pekanbaru No. 05 of 2022 concerning public order and the effectiveness of controlling illegal houses so that it can restore its original function so that the City of Pekanbaru is beautiful and orderly, creating peace and order for the community. The purpose of this research is to know and analyze the effectiveness of controlling illegal houses in Pekanbaru City and to find out the factors that influence the effectiveness of controlling illegal houses in Pekanbaru City. This research uses qualitative research and determines informants using purposive sampling and snowball techniques. Primary and secondary data obtained through observation, interviews and documentation are then analyzed based on the research problem. The results of the study show that : the effectiveness of illegal house control activities has not yet reached the target. Information on illegal houses received is still lacking because illegal houses are reported when there is interest, and socialization and cooperation are still lacking because both are carried out when there are activities Sto control illegal houses. The factors that influence the effectiveness of controlling illegal homes are the absence of sanctions and a lack of supervision. Keywords: Effectiveness, Control, Wild Houses